STUDY OF THE FUNCTIONAL AND NUTRITIONAL PROPERTIES OF DEFATTED OKRA POWDER AND OKRA PROTEIN ISOLATE AND CONCENTRATE - & Shakir, Kareem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The present study aimed to study the functional and nutritional properties of Defatted Okra Powder DOP and Okra Protein Concentrate OPC and Okra Protein Isolate OPI product from okra seeds (Abelmoschus esculentus), Essential amino acids 39.64, 40.93, 42.04% to DOP, OPC and OPI respectively, the theoretical biological value (BV) 66.12, 68.3, 69.94 for DOP, OPC and OPI respectively, the degree amino acid score (AAS) 104.01, 106.73, 109.23 respectively for the same groups and the same order, mineral ratio for phosphorus 1750, 2430, 110 mg/kg-1 of the three groups respectively, water absorption 1.82, 2.81, 3.36, fat absorption 2.03, 2.62, 3.03, foam capacity 58.1 0.64, 76.6%, and emulsion activity 50.23, 59, 60.38 m2/g-1.